Modelling studies of the hazards posed by liquid hydrogen use in civil aviation - Holborn, Paul; Ingram, J. M.; Benson, C. B. (IOP Publishing, 2022)
As part of the ENABLEH2 project, modelling studies have been carried out to examine liquid hydrogen release and dispersion behaviour for different LH2 aircraft and airport infrastructure leak/spill accident scenarios. The FLACS CFD model has been used to simulate the potential hazard effects following an accidental LH2 leak, including the extent of the flammable LH2 clouds formed, magnitude of explosion overpressures and pool fire radiation hazards. A comparison has also been made between the relative hazard consequences of using LH2 with conventional Jet A/A-1 fuel. The results indicate that in the event of accidental fuel leak/spill LH2 has some safety advantages over Jet A/A-1 but will also introduce additional hazards not found with Jet A/A-1 that will need to be carefully managed and mitigated against.